The timing of acid-induced increase in saliva secretion in transplanted submandibular glands. Issue 8 (August 2015) - Liu, X.J.; Li, M.; Su, J.Z.; Xie, Z.; Yu, G.Y.
Abstract The purpose of this study was to determine the timing of acid-induced increase in saliva secretion and to investigate the possibility of parasympathetic reinnervation of transplanted submandibular glands (SMGs). Citric acid stimulation-induced changes in secretion of transplanted SMGs were evaluated in 27 patients who underwent SMG transplantation for keratoconjunctivitis sicca (KCS); 99mTc scintigraphy and Schirmer tests were done at 1, 3, 6, and 9 months after transplantation. Acetylcholinesterase staining was conducted to confirm the presence of parasympathetic reinnervation in three SMGs at 6 and 9 months after transplantation. Schirmer tests showed significantly increased secretion of the transplanted SMGs after acid stimulation at 6 and 9 months, but not at 1 and 3 months. On 99mTc scintigraphy, no decline was detected on the dynamic time–activity curve after acid stimulation at 1 and 3 months, but a decline was detected in nine glands at 6 months and in 19 glands at 9 months. No decline was observed in the remaining eight glands at 9 months after transplantation. The histology findings were consistent with scintigraphy results. In conclusion, acid-induced increase in saliva secretion occurs at ≥6 months after SMG transplantation, and parasympathetic reinnervation of the transplanted SMG might occur.